Dinamika Kelembagaan dan Permasalahan Interaksi Lembaga: Studi Kasus Wisata Desa Karangrejo, Kecamatan Borobudur, Magelang - Beryl, Chansya; Satriawan, Ferdhika Riki; Dahlia, Ira; Azzahra, Miladia; Khairunisa, Vinda Permata; Zalzabila, Zalzabila (JURNAL NASIONAL PARIWISATA, 2024)
Community Based Tourism (CBT) is a variation of the tourism model that is widely applied in tourist destinations. This study explores the institutional dynamics and interaction problems in tourism management in Karangrejo Village, Borobudur District, Magelang, Indonesia. This is based on the challenges faced by Karangrejo Village in managing effective and sustainable tourism. This study aims to analyze institutional dynamics and the problems and complexity of interactions between stakeholders in Karangrejo Village. The study uses a qualitative-descriptive approach with primary and secondary data sources obtained through interviews, observations, and document studies. The results indicate that tourism management in Karangrejo Village is based on community initiatives with the village government acting as a supporter. This study also notes unique relationship patterns between stakeholders based on family and friendship, as well as adaptation to the COVID-19 crisis with assistance from external institutions, namely UNESCO. The conclusion emphasizes the importance of an adaptive and collaborative approach in village tourism management, with a deep understanding of the local context and strategic partnerships between stakeholders to ensure sustainable tourism development and empower local communities. Further research is needed on the institutional resilience of CBT management that is fluid during crisis conditions.